STUDENTSâ€™ INTRINSIC MOTIVATION TOWARD ENGLISH SUBJECT - Nurliessya, Rachmahditha Mega; Sada, Clarry; Susilawati, Endang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractStudying English in school as part of the main subject where it became important. This intrinsic motivation was investigated in order to know what kind of intrinsic motivation that could push or pull the students to make them interested in studying English subject. The subject for this research was the Twelfth GradeSMAN2 Pontianak. The data showed that Satisfaction is the most intrinsic motivation that could affect their study with 74.92%. While the statement that shows the students motivation is â€œbecause I feel English is an important language in the economic development of the worldâ€ got 82.94%. This percentage shows studentsâ€™ main reason to study English subject werenâ€™t only because of the important language in the economic development of the world, but also general satisfaction for the students themselves and is considered as the Intrinsic Motivation could really affect their study of English Subject. It proves that the students have their Intrinsic Motivation, especially in satisfaction category.Â Keyword : Studentsâ€™ Intrinsic Motivation, English Subject